b - Levstik, Linda S.; Barton, Keith C. (b, 2001)
"Doing History offers a perspective on history instruction in the elementary and middle grades. Through case studies of teachers and students in diverse classrooms and from diverse backgrounds, the text shows children engaging in authentic historical investigations, often in the context of an integrated social studies curriculum."
Includes bibliographical references and index.
Keywords: v; History -- Study and teaching (Middle school) -- United States